Neurophysiological Indices of Speech and Nonspeech Stimulus Processing. - Tampas, Joanna W.; Harkrider, Ashley W.; Hedrick, Mark S. (Journal of Speech, Language & Hearing Research, 2005)
Auditory event-related potentials (mismatch negativity and P300) and behavioral discrimination were measured to synthetically generated consonant-vowel (CV) speech and nonspeech contrasts in 10 young adults with normal auditory systems. Previous research has demonstrated that behavioral and P300 responses reflect a phonetic, categorical level of processing. The aims of the current investigation were (a) to examine whether the mismatch negativity (MMN) response is also influenced by the phonetic characteristics of a stimulus or if it reflects purely an acoustic level of processing and (b) to expand our understanding of the neurophysiology underlying categorical perception, a phenomenon crucial in the processing of speech. The CVs were 2 within-category stimuli and the nonspeech stimuli were 2 glides whose frequency ramps matched the formant transitions of the CV stimuli. Listeners exhibited better behavioral discrimination to the nonspeech versus speech stimuli in same/different and oddball behavioral paradigms. MMN responses were elicited by the nonspeech stimuli, but absent to CV speech stimuli. Larger amplitude and earlier P300s were elicited by the nonspeech stimuli, while smaller and longer latency P300s were elicited by the speech stimulus contrast. Results suggest that the 2 types of stimuli were processed differently when measured behaviorally, with MMN, or P300.The better discrimination and clearer neurophysiological representation of the frequency glide, nonspeech stimuli versus the CV speech stimuli of analogous acoustic content support (a) categorical perception representation at the level of the MMN generators and (b) parallel processing of acoustic (sensory) and phonetic (categorical) information at the level of the MMN generators. Reprinted by permission of the publisher.